PTU-054 Transnasal Gastroscopy – Are The Biopsies Suitable For Barrett's Surveillance?. (9th June 2014) - Fox, S
Abstract : Introduction: Transnasal gastroscopy is a far more acceptable form of gastroscopy to the patient, with benefits including reduced gagging, ability to communicate during the procedure, greater flexibility of endoscope allowing easier visualisation of difficult areas and closer inspection of the laryn x. 1 Due to the smaller working channel, 2.0mm as compared with 2.8 mm of a standard oral gastroscope, the biopsy forceps used in transnasal gastroscopy are smaller, leading to questions about the suitability of transnasal gastroscopy for Barrett's surveillance. As an early adopter of transnasal gastroscopy, Braintree community hospital endoscopy service has performed many thousands of diagnostic transnasal gastroscopies including Barrett's surveillance. This study compares the dysplasia and malignancy rate of transnasal gastroscopy biopsies and oral gastroscopy biopsies. Methods: All patients attending for a follow up gastroscopy for Barrett's surveillance over the past three years were included in the study. Patients attending for gastroscopy are sent information on the types of procedure when the appointment is booked. The patient is free to choose whichever form of gastroscopy they wish. On admission, the nurse will explain both procedures again and the patient will then choose. The vast majority choose to have transnasal gastroscopy. For those that choose to have oral gastroscopy, a standard oral gastroscope is used rather than a transnasal gastroscope. All endoscopists take quadrantic biopsies of the Barrett's segment in accordance with the BSG guidelines. The study looked back at 3 years of Barrett's surveillance and compared the rates of dysplasia found in the transnasal series and the oral series. The overall dysplasia rate, including adenocarcinoma, was compared. Results: In the three year period there were a total of 1282 patients who underwent Barrett's surveillance. Of these, 905 (70.6%) chose to have transnasal gastroscopy, the remainder, 377 (29.4%) chose to have oral gastroscopy. Of the transnasal series, 12 (1.3%) had LGD, 5 (0.6%) had HGD, 3(0.3%) had ACA and 9 (1%) were indefinite for dysplasia. Of the oral series, 7 (1.8%) had LGD, 0(0%) had HGD, 2(0.5%) had ACA and 7 (1.8%) were indefinite for dysplasia. The overall dysplasia and malignancy rate in the trans nasal group versus the oral group was 2.2% vs. 2.4% (p = 0.4048). Conclusion: Our series at Braintree community hospital shows that there is not a significant difference in the dysplasia and malignance rate found on transnasal biopsies as compared with oral gastroscopy biopsies. Reference: Knuth J, Kunze DE, Benz C, Bullian DR, Heiss MM, Lefering R, Saad S, Saers T, Krakamp B. Is the transnasal access for esophagogastroduodenoscopy in routine use equal to the transoral route? A prospective, randomized trial. Z Gastroenterol 2013 Dec;51(12):1369–1376 Disclosure of Interest: None Declared.